2020
DOI: 10.1093/ejcts/ezaa274
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity associated with poorer outcomes in patients undergoing minimally invasive mitral valve surgery?

Abstract: Graphical Abstract OBJECTIVES High body mass index (BMI) makes minimally invasive mitral valve surgery (MIMVS) more challenging with some surgeons considering this a contraindication. We sought to determine whether this is because the outcomes are genuinely worse than those of non-obese patients. METHODS This is a retrospective cohort study of all patients undergoing MIMVS ± concomitant proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Five-year outcomes were reported with rates of mortality, stroke, AKI, DSWI and reoperation for bleeding provided. 40 Boukhris et al retrospectively analysed the outcomes of 412 TAVR patients with underweight (<20 kg/m 2 ), normal weight (≥20 to <25 kg/m 2 ), overweight (≥25 to <30 kg/m 2 ) and obesity (≥30 kg/m 2 ). Postoperatively, patients were followed for 1 year.…”
Section: Background Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Five-year outcomes were reported with rates of mortality, stroke, AKI, DSWI and reoperation for bleeding provided. 40 Boukhris et al retrospectively analysed the outcomes of 412 TAVR patients with underweight (<20 kg/m 2 ), normal weight (≥20 to <25 kg/m 2 ), overweight (≥25 to <30 kg/m 2 ) and obesity (≥30 kg/m 2 ). Postoperatively, patients were followed for 1 year.…”
Section: Background Informationmentioning
confidence: 99%
“…32 The studies conducted by Aljanadi, Bruno, De Marzo, Forgie, Ho, Keller, Nazir, Rapetto, Smith and van der Boon did not find significant differences in mortality rates between their groups. 11,15,16,25,40,43,46,48,49,52…”
Section: Postoperative Mortalitymentioning
confidence: 99%
“…9 Aljanadi et al found that five-year survival between obese and non-obese patients undergoing minimally invasive mitral valve surgery was similar (95.8% vs 95.5%, p=0.83). 10 In consideration of the patient with obesity, Santana et al demonstrated minimally invasive approaches to be superior to full sternotomy with fewer postoperative complications (23.5% vs 51.0%, p=0.034) and lower in-hospital mortality (0% vs 8.3%, p=0.04). 4 However, to date, these observations have not been scrutinized between obesity classes, raising question of the broad application of these findings across the continuum of higher BMIs.…”
Section: Discussionmentioning
confidence: 99%
“…Median-term results reported on obese minimally invasive mitral surgery patients showed no difference in survival to nonobese patients. 15,25 Robotic surgery has no shortcomings in allowing adequate mitral repair and avoidance of adverse events in the early period which can result in better long-term survival in obese patients with more co-existing comorbidities. These high-risk patients are not selected for robotic surgery in some institutions and may not be selected in the early periods of the learning curve.…”
Section: Statisticsmentioning
confidence: 99%